IMPLEMENTING PROBLEM-BASED LEARNING TO ENHANCE PANCASILA EDUCATION OUTCOMES IN GRADE IV AT ELEMENTARY SCHOOL - Nada Yumna Hanifah; Lisa Retnasari; Ella Kusuma Wardani; Muhammad Alfarizqi Nizammuddin Ghiffari (Universitas Majalengka, 2025)
The low learning outcomes in Pancasila Education among Grade IV students at SD Negeri Golo Yogyakarta highlight the need for innovative teaching strategies. This research aims to improve students' learning outcomes by implementing a Problem-Based Learning (PBL) model for Pancasila Education under the framework of the Merdeka Curriculum. The study adopts a classroom action research (CAR) approach using the Kemmis and McTaggart model, which involves four stages: planning, action, observation, and reflection. The research was conducted over two cycles, utilizing pretest-posttest, observation, and documentation as data collection methods. Data were analyzed using both qualitative and quantitative techniques to evaluate learning outcomes and student engagement. The findings demonstrate that the PBL model effectively enhances students' cognitive skills and engagement in Pancasila Education. Learning outcomes showed consistent improvement across the cycles, indicating the relevance of PBL in fostering critical thinking and understanding of Pancasila values. The study underscores the importance of contextual and student-centered learning methods in achieving educational objectives aligned with the Merdeka Curriculum.